Down and High: Reflections Regarding Depression and Cannabis - Langlois, Catherine; Potvin, Stéphane; Khullar, Atul; Tourjman, Smadar Valérie (Frontiers in Psychiatry, 2021)
In light of the recent legalization of cannabis in Canada, the understanding of the potential impact of the use of cannabis by individuals suffering from depression is increasingly important. It is fundamental that we look into the existing literature to examine the influence legal recreational marijuana could have on our society and psychiatric diseases. In this article, we will explore the relationship that exists between depression and cannabis, the impact of cannabis on the course and clinical presentation of depression, cognitive effects and considerations of treatment. We have undertaken a wide-ranging review of the literature in order to address these questions. Although the breadth and quality of the literature is not such that definitive statements can be made regarding the relationships of cannabis with various dimensions, some tentative conclusions can be gleaned regarding alterations in clinical manifestations, functioning, cognition (1) and treatment avenues.